Improving social skills and learning outcomes of fifth-grade students through contextual learning - Hanoatubun, Lenny; Wibowo, Setiawan Edi; Sayekti, Octavian Muning (Jurnal Penelitian Ilmu Pendidikan, 2024)
This study employs an action research method consisting of planning, implementation, observation, and reflection to enhance elementary students’ social skills and learning outcomes at Private Elementary School SYPPK Salib Suci Agats. The research follows a classroom action research model as outlined by Kemmis and McTaggart. Fifth-grade students (20 in total) at Private Elementary School YPPK Salib Suci Agats served as the subjects. Data was collected through both test and non-test techniques. Various assessment instruments, such as descriptive problem-solving tests, attitude rating scales, and learning implementation observation sheets, were used to gather data. The initial findings showed that only 5 out of 20 students (25%) achieved scores above the Minimum Mastery Criterion (MMC), indicating they met the required competency. After the first action cycle, the number of students scoring above the MMC increased to 11 students (55%), while 9 students (45%) remained below the MMC, necessitating a second cycle. Following reflections on the first cycle, certain shortcomings were identified (particularly the less-than-optimal use of learning media), which were addressed in the second cycle by incorporating concrete learning media. As a result, by the end of the second cycle, 17 students (85%) scored above the MMC. This improvement demonstrates the effectiveness of contextual learning in raising both the social skills and academic performance of the students.